Comprehensive Treatment of Severe Follicular Occlusion Triad: A Case Report - Yang K; Shi M; Fu C; Huo R (Dove Medical Press, 2022)
Kun Yang,1 Mengdong Shi,1 Cong Fu,2,* Ran Huo1,2,* 1Department of Plastic Surgery, Shandong Provincial Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People's Republic of China; 2Department of Plastic Surgery, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of China*These authors contributed equally to this workCorrespondence: Cong Fu; Ran Huo, Tel +86 15154101889 ; +86 15168889001, Fax +860531-68778153, Email cong3399@outlook.com; huoran@medmail.com.cnAbstract: Follicular occlusion triad (FOT) is a chronic inflammatory skin disease that comprises hidradenitis suppurativa, acne conglobata, and perifolliculitis capitis abscedens et suffodiens and can seriously affect a patient's quality of life. Currently, there is no consensus on the treatment plan for FOT. There are also only a few reports on the treatment of severe FOT. In July 2020, a male patient who was diagnosed with severe FOT was treated in our hospital and received comprehensive surgical treatment for 2 months. This treatment strategy was effective and the patient had no recurrence during a follow-up period of > 1 year. By retrospectively analyzing the clinical data of the patient, recording the patient's condition during postoperative recovery, and reviewing relevant literatures, the clinical manifestations, diagnosis, choice of treatment methods, and prognosis of FOT were evaluated.Keywords: chronic inflammatory skin disease, comprehensive treatment, surgical management